Beyond Epistemology - Weiss, F.G. author. aut Link
254 p.
Keywords: This book approaches Hegel from the standpoint of what we might call the question of knowledge. Hegel, of course, had no "theory of knowledge" in the narrow and abstract sense in which it has come to be understood since Locke and Kant. "The examination of knowledge," he holds, "can only be carried out by an act of knowledge," and "to seek to know before we know is as absurd as the wise resolution of Scholasticus, not to venture into the water until he had learned to swim. " * While Hegel wrote no treatise exclusively devoted to epistemology, his entire philosophy is nonetheless a many-faceted theory of truth, and thus our title - Beyond Epistemology - is meant to suggest a return to the classical meaning and relation of the terms episteme and logos. I had originally planned to include a lengthy introduction for these essays, setting out Hegel's general view of philosophic truth. But as the papers came in, it became clear that I had chosen my contributors too well; indeed, they have all but put me out of business. In any case, it gives me great pleasure to have been able to gather this symposium of outstanding Hegel scholars, to provide for them a forum on a common theme of great importance, and especially, thanks to Arnold Miller, to have Hegel himself among them. Frederick G. Weiss Charlottesville, Va. • The Logic of Hegel, trans. from the Etu; yclopaedta by William Wallace. 2nd ed.